Non-Covalent Interactions Atlas Benchmark Data Sets: Hydrogen Bonding - Řezáč, Jan (Journal of chemical theory and computation, 2020)
The Non-Covalent Interactions Atlas project (www.nciatlas.org) aims to cover a wide range of noncovalent interactions with a new generation of benchmark data sets. This Article presents the first two data sets focused on hydrogen bonding: HB375, featuring neutral systems, and IHB100 for ionic H-bonds. Both data sets are complemented by 10-point dissociation curves (HB375×10, IHB100×10). The interaction energies are extrapolated to the CCSD(T)/CBS limit from calculations in large basis sets. The Article also summarizes the design principles that will be used to construct the subsequent data sets in the series. The testing of DFT-D methods on the HB375 set has revealed interesting, previously unnoticed issues. The application of the new data to the testing and parametrization of semiempirical QM methods is also discussed.